APLIKASI PUPUK HAYATI DAN AZOLLA UNTUK MENGURANGI DOSIS PUPUK ANORGANIK DAN MENINGKATKAN N, P, C ORGANIK TANAH, DAN N, P TANAMAN, SERTA HASIL PADI SAWAH - Mieke Rochimi Setiawati; Betty Natalie Fitriatin; Pujawati Suryatmana; Tualar Simarmata (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2020)
Biofertilizers and Azolla are local potentials sources that can be used for inorganic fertilizers efficiency in increasing crop yields. The purpose of this study was to determine the dose of inorganic fertilizers that can be reduced by the application of biofertilizers and Azolla in lowland rice plants. The aims of study was to determine the increase in N plants, N soil, available P, P uptake, C organic, and the yield of lowland rice. The experiment was carried out at the Experimental Field, Ciparanje, Faculty of Agriculture, Padjadjaran University, in Jatinangor. The treatment in this experiment were A = without the use of fertilizer, B = NPK 100% Fertilizer of recommended dosage, C = 0% NPK + Biofertilizer + Azolla, D = 25% NPK + Biofertilizer + Azolla, E = 50% NPK + Biofertilizer + Azolla, and F = 75% NPK + Biofertilizer + Azolla. The study design used was a Randomized Block Design with four replications. The results showed that biofertilizer and Azolla combined with inorganic fertilizers can enhance total N soil, N plants, P available soil, P uptake of plants, and C organic soil. Application 50% NPK + Azolla + biofertilizer could increased Milled Dry Grain by 10.82% compared to the recommended dosage of inorganic fertilizer (100% NPK) and caould decrease the use of inorganic fertilizer by 50%.